1997
DOI: 10.1016/s0022-1694(96)03322-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface water redistribution in an area of patterned vegetation in a semi-arid environment, south-west Niger

Abstract: The surface hydrology of a semi-arid area of patterned vegetation in southwest Niger is described. In this region alternating bands of vegetation and bare ground aligned along the contours of a gently sloping terrain give rise to a phenomenon known as 'brousse tigrée' (tiger bush). At the selected study site the vegetation bands are 10-30 m wide, separated by 50-100-m-wide bands of bare ground. Five species of shrub dominate, Guiera senegalensis, Combretum micranthum, C. nigricans, Acacia ataxacantha and A. ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
134
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(140 citation statements)
references
References 31 publications
3
134
0
2
Order By: Relevance
“…1a), and gap patterns with bare spots in the vegetation with a diameter of 5-20 m ( fig. 1b; Bromley et al 1997;Aguiar and Sala 1999;Ludwig et al 1999b;Valentin et al 1999;Couteron and Lejeune 2001). On slopes steeper than 0.2% in arid regions, typical regular-banded vegetation patterns with a band width in the range of a few tens of meters are observed (Klausmeier 1999;Leprun 1999;Valentin et al 1999;d'Herbes et al 2001).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…1a), and gap patterns with bare spots in the vegetation with a diameter of 5-20 m ( fig. 1b; Bromley et al 1997;Aguiar and Sala 1999;Ludwig et al 1999b;Valentin et al 1999;Couteron and Lejeune 2001). On slopes steeper than 0.2% in arid regions, typical regular-banded vegetation patterns with a band width in the range of a few tens of meters are observed (Klausmeier 1999;Leprun 1999;Valentin et al 1999;d'Herbes et al 2001).…”
mentioning
confidence: 97%
“…Vegetation patterning is generally linked to the mechanism by which plants increase surface-water infiltration into the soil, in combination with low annual rainfall conditions (Bromley et al 1997;Klausmeier 1999;Leprun 1999;Ludwig et al 1999a;HilleRisLambers et al 2001). During rain showers, some rainwater will infiltrate into the soil, while the remainder will run off as surface water to other areas.…”
mentioning
confidence: 99%
“…Extending to the scale of hillslopes or small catchments, additional variability of landscape characteristics influences the runoff redistribution. Characteristic sequences of surface types in terms of vegetation cover, soils and surface crusts with variable infiltration characteristics were shown for hillslope transects in semi-arid Africa by Perrolf and Sandström (1995), Bromley et al (1997) and D'Herbès and or for semi-arid Spain (Nicolau et al, 1996). Bergkamp (1998) distinguished in a hierarchical way five spatial scale levels by characteristic discontinuities in the geomorphological and soil properties, ranging from the terracette level, via various hillslope scales to the catchment scale.…”
Section: Landscape Variability and Hydrological Processes In Semi-arimentioning
confidence: 97%
“…This patchiness influences, on the one hand, total evapotranspiration rates of the land surface by the interaction of energy and momentum fluxes from bare and vegetated patches (Boulet et al, 1999). On the other hand, the patchiness gives rise to redistribution of runoff and associated sediments and nutrients, with bare soil surfaces tending to act as source areas of surface runoff and vegetated patches as sink areas, receiving runon from bare soil surfaces for re-infiltration (Puigdefabregas and Sanchez, 1996;Bromley et al, 1997;Reid et al, 1999;Valentin and d'Herbès, 1999;Cammeraat, 2002). Extending to the scale of hillslopes or small catchments, additional variability of landscape characteristics influences the runoff redistribution.…”
Section: Landscape Variability and Hydrological Processes In Semi-arimentioning
confidence: 99%
“…Meanwhile, though a positive effect of land abandonment on vegetation diversity has been found by several studies (Dana and Mota 2006;Donath et al 2007), a negative affect was also found by some (Rickert et al 2012;Jacquemyn et al 2011). In terms of vegetation patterns, much research focuses on a two-phase mosaic structure of high-and low-vegetation cover patches, which commonly presents itself in semi-arid ecosystems (Pellerin et al 2009;Puigdefabregas 2005;Bromley et al 1997;Cerda 1997;Wilcox et al 2003). Mechanisms of patch formation and dynamics have also been conducted (Mayor et al 2008;Liu et al 2013;Aguiar and Sala 1999;Bautista et al 2007).…”
Section: Introductionmentioning
confidence: 99%